Rescued [compact disc, unabridged] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2018)
Defense lawyer Andy Carpenter is reluctant to take on any more cases. He'd much rather spend his time working for his dog rescue organization, the Tara Foundation, than find himself back in a courtroom. However, when a truck carrying over seventy dogs from the South to the rescue-friendly northeast turns up with a murdered driver, Andy can't help but get involved.